Diagnostic difficulties of leptospirosis during pregnancy: a maternal near miss - Rajandran, Priyanka; Papa, Dasari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
A 24-year-old G2A1 at 34 weeks of gestation was admitted with complaints of nausea, vomiting, pedal edema and high blood pressure recordings. She developed imminent symptoms after admission for which she received prophylactic magnesium sulphate therapy and a provisional diagnosis of severe preeclampsia with imminent symptoms was made. With worsening hematological, liver and renal parameters as she did not fulfill the Swansea’s criteria for acute fatty liver of pregnancy (AFLP), partial hemolysis elevated liver enzymes and low platelet count (HELLP) was suspected. She was delivered by cesarean section. Infectious disease work up was sent in view of rising counts and elevated liver enzymes which was positive for leptospirosis. There was also history of walking in the rice fields bare foot and rat infestations in the fields supporting the diagnosis. Both the mother and baby were discharged in a healthy condition. The diagnosis becomes challenging in pregnancy as it mimics pregnancy induced hypertension, acute fatty liver of pregnancy, partial HELLP, obstetric cholestasis and viral hepatitis.